"Crying without tears" as an early diagnostic sign-post of triple A (Allgrove) syndrome: two case reports - Daniel Tibussek; Sujal Ghosh; Angela Huebner; Joerg Schaper; Ertan Mayatepek; Katrin Koehler (BMC, 2018)
Abstract Background Triple A syndrome (or Allgrove syndrome) is a rare autosomal recessive disorder characterized by alacrima, achalasia, adrenal insufficiency and autonomic/neurological abnormalities. The majority of cases are caused by mutations in the AAAS gene located on chromosome 12q13. However, the clinical picture as well as genetic testing may be complex since symptomatology is variable and mutations cannot be identified in all clinically diagnosed patients. We present two unrelated patients with triple-A syndrome illustrating the importance of alacrima as an early clinical sign. Case presentation A 3.5 year old girl presented with repeated hypoglycaemic myoclonic events. Adrenal insufficiency was diagnosed. In addition, alacrima, obvious since early infancy, was incidentally reported by the mother and finally lead to the clinical diagnosis of triple A syndrome. This was confirmed by positive mutation analysis of the AAAS gene. The second patient, an 8 months old boy was presented because of anisocoria and unilateral optic atrophy. MRI revealed cerebellar vermis hypotrophy. Psychomotor retardation, failure to thrive, and frequent vomiting lead to further diagnostic work-up. Achalasia was diagnosed radiologically. In addition, the mother mentioned absence of tears since birth leading to the clinical diagnosis of triple A syndrome. In contrast to the first cases genetic testing was negative. Conclusion These two patients illustrate the heterogeneity of triple A syndrome in both terms, clinical expression and genetic testing. We particularly aim to stress the importance of alacrima, which should be considered as a red flag symptom. Further differential diagnosis is required in every child affected by alacrima.